Occurrence and disappearance of parathion and malathion residues in vegetables and fruits - Koivistoinen, Pekka; Roine, Paavo; Jokela, Kirsti (Agricultural and Food Science, 1959)
Disappearance of parathion and malathion residues in 9 different kinds of fruits and vegetables (pea, cucumber, lettuce, strawberry, black currant, apple, stringbean broccoli and spinach) sprayed about two weeks before the normal harvest was investigated. In addition, experiments were made on the effects of 3 different conserving processes upon the residues on black currant as well as on the persistence of the residues in conserves and frozen products during storage. The determination of parathion was carried out by a modification of the method of AVERELL and NORRIS, using a benzene-water-alcohol mixture and increased acidity in the reduction. The malathion was determined by the method of NORRIS et al. with the modification of benzene used as the extracting solvent instead of carbon tetrachloride. The procedures for the determination of total residues in plants are described in detail. The initial deposits of parathion varied from 0.49 to 14.60 ppm and those of malathion from less than 0.5 to 49.8 ppm, depending on the plant species. The half-life of the residues was 1—3 and 1—2 days, respectively. The most persistent residues were found in black currant; in these berries malathion could be determined qualitatively 28 days and parathion at least 43 days after spraying. Very small residues were found in the steam-juice prepared from black currants. In the preparation of two kinds of jam, 30 and 54 % of the parathion and 54 and 71 % of the malathion were destroyed. Both of the pesticides were very stable in black currant conserves as well as in frozen products for a period of at least 6 months.